PENGARUH PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Astriani, Nurullita; Dhana, Muhammad Bayu Al (Mahesa Research Center, 2020)
This study aims to determine the effect of think pair share type of cooperative learning on students' mathematical representation abilities. This research is a quasi-experimental research. The population in this study were all eighth-grade students of SMP Negeri 1 Pangkalan Susu. The samples in this study were 2 classes, namely class VIII-1 which was used as an experimental class and class VIII-2 was used as a control class. The instrument used was a test in the form of a description of the material Relations and Functions. From testing the hypothesis obtained tcount (2.135) > ttable (1.6715) means that Ho is rejected and Ha is accepted. This shows the influence of think pair share type of cooperative learning on students' mathematical representation ability.